Comparison of outcomes of conventional WaveLight® Allegretto Wave® and Technolas® excimer lasers in myopic laser in situ keratomileusis - Han DC (Dove Medical Press, 2012)
Daphne CY Han,1,2 Jean Chen,3 Hla Myint Htoon,2 Donald TH Tan,1,2,4 Jodhbir S Mehta1,21Singapore National Eye Centre, 2Singapore Eye Research Institute, 3Yong Loo Lin School of Medicine, National University of Singapore, 4Department of Ophthalmology, Yong Loo Lin School of Medicine, National University of Singapore, SingaporeObjective: To compare the results of laser in situ keratomileusis for myopia using WaveLight® Allegretto Wave® Eye-Q® and Technolas® 217z excimer lasers.Method: A retrospective, comparative case series of 442 eyes matched for age and myopia: half each were treated with Allegretto's wavefront-optimized algorithm and Technolas PlanoScan. Outcome measures were postoperative mean logarithm of the minimum angle of resolution (logMAR) uncorrected visual acuity (UCVA), manifest refraction spherical equivalent (MRSE), cylinder, safety and efficacy indices, refractive predictability, and optical zone size selection. Refractive predictability of a subgroup treated for –2.50 to –4.0 diopter (D) was analyzed separately.Results: At mean follow-up of 80.5 days, mean logMAR UCVA, mean MRSE and mean postoperative cylinder were 0.02 ± 0.07 (range –0.12 to 0.30), 0.27 ± 0.36 D (range –1.25 to 1.50 D) and –0.33 ± 0.30 D (range 0.00 to –1.50 D) for Allegretto versus 0.02 ± 0.08 (range –0.12 to 0.40), 0.095 ± 0.47 D (range –1.25 to 1.13 D) and –0.44 ± 0.5 2 D (range 0.00 to –2.25 D) for Technolas (P = 0.98, 0.80 and 0.006). Mean safety and efficacy indices were 1.05 ± 0.13 (0.75–1.33) and 0.97 ± 0.13 (0.50–1.33) for Allegretto and 1.07 ± 0.14 (0.75–1.49) and 0.97 ± 0.17 (0.40–1.49) for Technolas (P = 0.23 and 0.69). Proportions of eyes achieving postoperative MRSE within ±1.0 D, ±0.5 D, and ±0.25 D were 98.2%, 91.9% and 75.6% for Allegretto and 99.1%, 97.8% and 72.4% for Technolas (P = 0.68, 0.20 and 0.51). Mean optical zone size selected was 6.48 ± 0.10 mm (range 6.0–6.5 mm) for Allegretto and 6.38 ± 0.19 mm (range 5.6–6.6 mm) for Technolas (P < 0.001). Of the subgroup with treatment between –2.5 and –4.0 D, 86.8% and 58.5% of eyes treated with Allegretto achieved postoperative MRSE within ±0.50 D and ±0.25 D versus 70.4% and 44.4% for Technolas (P = 0.006 and 0.057).Conclusion: No differences were seen in postoperative mean logMAR UCVA, MRSE, safety and efficacy indices between the two lasers. Allegretto produced less residual astigmatism, possibly improved refractive predictability, and required smaller optical zone selection.Keywords: LASIK, myopia, laser vision correction, conventional laser algorithm